Thinker and scholar Sheikh Abdel Hamid Ben Badis (مجلة إحالات, 2026)
He is one of the most prominent pioneers of the intellectual and reformist renaissance in Algeria inthe twentieth century. He is known for his significant role in resisting French colonialism, both culturally and religiously, by reviving the Islamic and Arab identity of the Algerian people. He called for adherence toAlgeria's Islamic and Arab identity, refusing assimilation into French culture. He worked tirelessly to establish the Association of Muslim Scholars.